On $(g,s)$-Continuous and $(π g,s)$-Continuous Functions - Ekici, Erdal (Sarajevo journal of mathematics, 2024)
New generalizations of contra-continuity called ($π g,s$)-continuity and ($g, s$)-continuity are presented. Characterizations and properties of ($π g,s$)-continuous functions are discussed.